1981
DOI: 10.1056/nejm198107303050501
|View full text |Cite
|
Sign up to set email alerts
|

Increased Adhesion of Erythrocytes to Endothelial Cells in Diabetes Mellitus and Its Relation to Vascular Complications

Abstract: We studied the adhesion of erythrocytes from 30 diabetic patients and 25 controls to human endothelial cells. Washed erythrocytes were labeled with 51Cr and added to confluent endothelial cells cultured from umbilical veins. After incubation at 37 degrees C, the nonadherent erythrocytes were removed by sequential washings. The percentage of erythrocytes adhering to cultured endothelium after each wash was significantly higher when erythrocytes were from diabetics than when they were from controls (P less than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
95
1
2

Year Published

1983
1983
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 198 publications
(99 citation statements)
references
References 16 publications
1
95
1
2
Order By: Relevance
“…AGE-modified structures, whether present on plasma proteins or diabetic red cells, display increased adhesivity for endothelium because of their binding to cell surface RAGE (4,(17)(18)(19) H-inulin in Fig. 1, A and B , respectively) across cell monolayers compared with normal red cells, which were comparable with untreated controls.…”
Section: Resultsmentioning
confidence: 72%
“…AGE-modified structures, whether present on plasma proteins or diabetic red cells, display increased adhesivity for endothelium because of their binding to cell surface RAGE (4,(17)(18)(19) H-inulin in Fig. 1, A and B , respectively) across cell monolayers compared with normal red cells, which were comparable with untreated controls.…”
Section: Resultsmentioning
confidence: 72%
“…In some previous studies, an increased PF concentration was found in diabetic patients with microalbuminuria [12,13], but this was not confirmed by other investigators [3,4]. The aim of this study was to clarify this controversial issue, and to evaluate the PF concentration as a possible marker for early diabetic nephropathy.…”
mentioning
confidence: 73%
“…Plasma fibronectin (PF) plays a role in erythrocyte or platelet adhesion to vascular endothelium or subendothelial collagen [3,4].…”
mentioning
confidence: 99%
“…[28][29][30][31] Anti-AGE antibodies or soluble RAGE inhibit the enhanced adhesion to endothelium when incubated with RBC from diabetic patients. 32 The accelerated clearance of diabetic rat RBC when infused in normal rats is prevented by the infusion of anti-RAGE antibody in the animal.…”
Section: -27mentioning
confidence: 99%